Protective Effect of Shexiang Baoxin Pill on Myocardial Ischemia/Reperfusion Injury in Patients With STEMI - Haixia Qin; Siyuan Li; Zhenbing Liu (Frontiers in Pharmacology, 2021)
Background: There is no definite effect in the treatment of myocardial ischemia/reperfusion (I/R) injury in patients with acute ST-segment elevation myocardial infarction (STEMI). We evaluated the protective effect of Shexiang Baoxin Pill (SBP) on I/R injury in STEMI patients.Methods: STEMI patients were randomly divided into a primary percutaneous coronary intervention (PPCI) group (n = 52) and a PPCI + SBP group (n = 51). The area at risk of infarction (AAR) and final infarct size (FIS) were examined by single-photon emission computed tomography (SPECT). I/R injury was assessed using myocardial salvage (MS) and salvage index (SI) calculated from AAR and FIS.Results: The ST-segment resolution (STR) in the PPCI + SBP group was significantly higher than that in the PPCI group (p = 0.036), and the peak value of high-sensitivity troponin T (hsTNT) was lower than that in the PPCI group (p = 0.048). FIS in the PPCI + SBP group was smaller than that in the PPCI group (p = 0.047). MS (p = 0.023) and SI (p = 0.006) in the PPCI + SBP group were larger than those in the PPCI group. The left ventricular ejection fraction (LVEF) in the PPCI + SBP group was higher than that in the PPCI group (p = 0.049), and N-terminal pro-B type natriuretic peptide (NT-proBNP) level in the PPCI + SBP group was lower than that in the PPCI group (p = 0.048).Conclusions: SBP can alleviate I/R injury (MS and SI), decrease myocardial infarction area (peak value of hsTNT and FIS), and improve myocardial reperfusion (MBG and STR) and cardiac function (LVEF and NT-proBNP).